PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN DI PT.TRI DHARMA PUSAKA JAKARTA SELATAN - Nurul Giswi Karomah; Aldiansyah Aldiansyah (JURNAL LENTERA BISNIS, 2019)
This research was conducted with the aim to find out how the Compensation Effect on Employee Performance and learn more deeply the importance of compensation in the company and how much influence it has on employee performance. And the company that is the object of this research is PT. Tri Dharma Pusaka, South Jakarta. The method used in this study is a quantitative descriptive research method, where data is collected through questionnaires or questionnaires. Data collected through the results of the questionnaire are then processed with statistics, then interpreted, analyzed, and described according to the research objectives. The population and sample in this study were 55 people using saturated samples where all populations were sampled. Based on the results of the study, it can be seen that the effect of compensation has the results of the product moment correlation coefficient obtained r = 0.794, which means there is a positive relationship between compensation for employee work performance. The coefficient of determination  shows that Variable Compensation (X) affects the variable Employee performance (Y) of 63% while the rest is (100% - 63%) = 37% influenced by other factors not examined by the author. With a level of significance, because tcount is greater than t table (9.506> 1.674), then Ho is rejected and Ho is accepted, so it is concluded that there is a positive and significant influence between Compensation on the performance of employees at PT. Tri Dharma Pusaka, South Jakarta.Keywords; Compensation, work, performance